Mistakes as a source for learning – translation into a foreign language as a way of improving the linguistic and translation competence of the learner on academic translation courses - Teshajev Sunderland, Eva (Glottodidactica, 2018)
This article explores the problems which occur when teaching the translation of functional texts into a foreign language (from Polish into German). The article especially focuses on lexicalterminological and pragmatic translation mistakes, their causes, and strategies for avoiding them. One of the biggest challenges when translating into a foreign language is to use correct and adequate equivalents. The authors argue that the competences needed for this task should be taught as early as possible during translation training. The authors have therefore analysed texts translated by BA translation students and have chosen examples which represent the most frequent categories of mistakes, e.g. word-to-word translation, breaching the target language‘s conventions, and (inter)cultural problems. The solutions proposed are based on functional translation theory and translation criticism, and also take into account the classifications of mistakes used in translation didactics.